High dose of d-chiro-inositol improves oocyte quality in women with polycystic ovary syndrome undergoing ICSI: a randomized controlled trial. (3rd May 2020) - Mendoza, Nicolas; Galan, Maria Isabel; Molina, Cristina; Mendoza-Tesarik, Raquel; Conde, Cristina; Mazheika, Maryna; Diaz-Ropero, Maria Paz; Fonolla, Juristo; Tesarik, Jan; Olivares, Monica
Abstract: The aim of this study was to evaluate the effect of two doses of d -chiro-inositol (DCI) in combination with Myo-inositol (MYO) on the oocyte quality (OQ) of women with polycystic ovarian syndrome (PCOS) undergoing intracytoplasmic sperm injection (ICSI). Methods: This was a controlled, randomized, double-blind, parallel group study on 172 oocytes from 11 women. The study compared the effect of two MYO-DCI formulations given over 12 weeks on OQ. Five women received 550 mg of MYO + 300 mg of DCI daily (high DCI content group), while 6 women were given a daily dose of 550 mg of MYO with the only 27.6 mg of DCI (low DCI content group). Results: According to a multivariate analysis using linear mixed effect models, high doses of DCI have a positive influence on the quality of the cytoplasm of the oocyte ( β = 1.631, χ 2 = 7.347, d.f. = 1, p = .00672). Zona pellucida, plasma membrane, cytoplasm, and sperm reception have also been improved with any combination of MYO/DCI by decreasing testosterone or improving insulin sensitivity, regardless of age and body mass index. Conclusion: The combination of MYO with high doses of DCI improved oocyte cytoplasm quality in women with PCOS undergoing ICSI.